Genomic mapping of binding regions for the Ecdysone receptor protein complex - Gauhar, Zareen; Sun, Ling V.; Hua, Sujun; Mason, Christopher E.; Fuchs, Florian; Li, Tong-Ruei; Boutros, Michael; White, Kevin P.

(untitled) (Genome Research, 2009)
We determined the physical locations of the heterodimeric Ecdysone receptor/Ultraspiracle (ECR/USP) nuclear hormone receptor complex throughout the entire nonrepetitive genome of Drosophila melanogaster using a cell line (Kc167) that differentiates in response to 20-hydroxyecdysone (20-HE). 20-HE, the natural ligand of this complex, controls major aspects of insect development, including molting, metamorphosis, and reproduction. Direct gene targets of 20-HE signaling were identified by combining this physical binding-site profiling with gene expression profiling after treatment with 20-HE. We found 502 significant regions of ECR/USP binding throughout the genome. Only 42% of these regions are nearby genes that are 20-HE responsive in these cells. However, at least three quarters of the remaining ECR/USP regions are near 20-HE-regulated genes in other tissue and cell types during metamorphosis, suggesting that binding at many regulatory elements in the genome is largely noncell-type specific. The majority (21/26) of the early targets of 20-HE encode transcriptional regulatory factors. To determine whether any of these targets are required for the morphological differentiation of these cells, we used RNAi to reduce the expression of each of the 26 early genes. Accordingly, we found that three direct targets of ECR/USP—hairy, vrille, and Hr4—are required for cellular differentiation in response to the hormone. Initial mutational analysis of vrille in vivo reveals that it is required for metamorphosis.